2004
DOI: 10.1016/j.jtcvs.2003.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Long-term patency of coronary grafts with endoscopically harvested saphenous veins determined by contrast-enhanced electron beam computed tomography

Abstract: These data compare favorably with reported patency rates for traditionally harvested saphenous veins. Endoscopic saphenous vein harvesting, in addition to previous favorable reports on pain, complications, and costs, is now shown to provide comparable or better patency rates in comparison with traditionally harvested veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
1
14
0
2
Order By: Relevance
“…Acute perioperative events that might be associated with severe graft trauma have been observed for both endoscopic and open harvest techniques with similar frequencies [8]. However, premature graft failure that might be attributed to EVH has not been reported in long term follow-up [14][15][16][17]23]. In our series we did not find any early graft failure, clot formation in the harvested vein nor increased perioperative or intraoperative myocardial infarction.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Acute perioperative events that might be associated with severe graft trauma have been observed for both endoscopic and open harvest techniques with similar frequencies [8]. However, premature graft failure that might be attributed to EVH has not been reported in long term follow-up [14][15][16][17]23]. In our series we did not find any early graft failure, clot formation in the harvested vein nor increased perioperative or intraoperative myocardial infarction.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, the short-term 6 month patency rate of EVH veins, as assessed by contrast-enhanced electron beam computed tomography [16] Allen et al [14] showed similar 5-year event-free survival rates (freedom from death, myocardial infarction, recurrent angina, or congestive heart failure) 75% endoscopic versus 74% open harvest, p ¼ 0.85.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent angiographic studies of patency rates and scanning electron microscopy (SEM) assays of intimal integrity have disputed these conclusions [2,11,15]. Davis et al analysed the long-term (approximately 3 years) patency of vein grafts using contrast-enhanced electron beam CT and showed that graft patency rate of endoscopically harvested veins was better than that of traditionally harvested veins [16]. Studies analysing long-term outcome of EVH have even reported a significant reduction in mortality (hazard ratio 0.74) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Davis et al analysed the long-term (approximately 3 years) patency of vein grafts using contrast-enhanced electron beam CT and showed that graft patency rate of endoscopically harvested veins was better than that of traditionally harvested veins [16]. Studies analysing long-term outcome of EVH have even reported a significant reduction in mortality (hazard ratio 0.74) [16]. The overall patency rate depends on the target and vein-related variables and patient characteristics rather than the method of vein harvesting [8].…”
Section: Discussionmentioning
confidence: 99%